Numerical study of rolling process on the plastic strain distribution in wire + arc additive manufactured Ti-6Al-4V - Abbaszadeh, Masoud; Hönnige, Jan Roman; Filomeno, Martina; Kashaev, Nikolai; Williams, Stewart W.; Klusemann, Benjamin (American Institute of Physics (AIP), 2019)
Wire+arc additive manufacturing (WAAM) is an additive manufacturing (AM) process that employs wire as the feedstock and an arc as energy source, to construct near net-shape components at high build rates. Ti-6Al-4V deposits typically form large columnar prior β grains that can grow through the entire component height, leading to anisotropy and lower mechanical properties, compared to the equivalent wrought alloy. Cold-working techniques such as rolling can be used to promote grain refinement in Ti-6Al-4V WAAM parts, thus increasing strength and eliminating anisotropy concomitantly. Additionally, rolling can be beneficial in terms of reduction of residual stress and distortion. The aim of this study is to illustrate the effect of rolling process parameters on the plastic deformation characteristics in Ti-6Al-4V WAAM structures. To produce a certain refinement of the microstructure, a certain amount of strain is typically required; thus suitable design guidelines for practical applications are needed. The effect of different rolling process parameters, in particular, rolling load and roller profile radius on the plastic strain distribution is investigated based on the finite element method. From a numerical point of view, the effect of the stiffness of the roller is investigated, e.g. deformable vs. rigid roller. Results indicate that for an identical rolling load, the deformable roller produces lower equivalent plastic strains due to its own elastic deformation. Additionally, a lower friction coefficient produces higher equivalent plastic strains near the top surface but, it has an insignificant effect on the plastic deformation further away from the top surface. However, numerically the computation time significantly increased for a higher friction coefficient. Larger roller profile radii lead to lower plastic strain near the top surface, but simultaneously had nearly no noticeable effect on plastic strains at deeper depth. In addition, the effect of interspace between rollers on the uniformity of the plastic strain during multi-pass rolling was investigated for a selected example. The results show that a higher uniform plastic strain distribution is obtained when the interspace between two rollers is equal to the residual width of the groove produced by a single rolling pass